PENGARUH KETRAMPILAN MENGAJAR GURU TPQ TERHADAP PEMAHAMAN MEMBACA AL-QUR’AN PADA ANAK DIDIK DI MASJID SHIRATHAL JANNAH KELURAHAN DINOYO KOTA MALANG - Faisol Amin; Azhar Haq; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The qur'an education park (TPQ) is one of the non-formal education units related to religion, the main material is the Qur'an and many other materials that are taught such as learning about prayer materials, fiqh, and morality. a TPQ teacher to form the soul of the qur'an of the students, one of which is to be able to read the Al-qur'an well and be able to understand the meaning and content in the Qur'anic verses. In this study, respondents consisting of students were submitted to an indirect and closed questionnaire. TPQ teacher teaching skills (Variable X) given to students. The variable Y (reading comprehension of the students' Al-quran). the interpretation of the value of the product moment is known that the r value of work is 0.940, then the second alternative hypothesis (Ha) proposed which reads: TPQ teacher teaching skills have a high influence on reading comprehension of the Qur'an. the characteristics of an activity can be called learning if the activity produces a change in a person in the form of a change occurs consciously, is functional, has a positive active nature, not temporary, includes all behavior, and aims or directed.